Readings in welfare economics : a selection of papers from the review of economic studies - Farrell, M.J. (London : Macmillan ; New York : St. Martin's Press, 1973)
A Selection of articles published in the Review of Economic Studies.
Includes bibliographical references.
rpm 06/11/2017
Loans
Keywords: Welfare economics